Development and assessment of implant material sustainability in synthesized AV fistula assisting device - Raut, Abhijeet; Uddanwadikar, V. R.; Padole, P. M.; Ookalkar, D.; Kanekar, Jugal (Materials Research Express, 2025)
Arteriovenous fistula (AVF) failure remains a significant challenge in the treatment of end-stage renal disease, leading to increased morbidity and economic burden to the patients. The availability of effective devices to address AVF is still very limited globally. In view of the high failure rate of AVF during hemodialysis, development and selection of most appropriate material for AVF device is a test for the researcher. In the present research work, the mechanical and biocompatibility tests have been conducted on the implant grade silicon materials selected to develop the device before it is subjected to animal trials. The AVF assisting device is fabricated and a custom-designed in-vitro model is developed to replicate the human anatomical surroundings. The tensile strength and the elongation of the selected implant-grade silicon in the fabricated device are tested using a universal testing machine; also, the surface structure and the chemical composition are tested using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) respectively. The hydrophilicity and long-term performance are analyzed using a water absorption test. The biocompatibility and cytotoxicity of the material and fabricated device are determined using cell viability assay. It is observed that the silicone material used in the AVF assisting device shows strong mechanical integrity, optimum structural stability, biocompatibility and is non-cytotoxic to mammalian cell line. Thus, it can be concluded that the implant-grade silicone material is a potential candidate for the design and development of AVF assisting device due to its observed sustainability and biocompatibility.
Keywords: arteriovenous fistula (AVF) failure; AV fistula assisting device; hemodialysis; material characterization